Aesthetics of nature in contemporary context - Popović, Una, filozofkinja (Array, 2019)
Aesthetic of nature is in this paper presented in the context of its revival in contemporary philosophy. Nature as the object of aesthetic experience and valorisation is mainly a question of traditional aesthetics, so its revival is here presented as the problem of redefinition of aesthetics in contemporary terms. The analysis encompasses examples from contemporary aesthetics, philosophy and art, and it is focused on revealing the key features of new aesthetic understanding of nature. These key features are in conclusion seen as indications of the future perspective of the development of philosophical aesthetics.